Análisis del impacto social y económico del desempleo en la ciudad de Quevedo periodo 2010 - Vilcacundo Flores, Kerly Alexandra (2012)
This investigative work was performed to analyze the social and economic impact of the unemployment in the city of Quevedo, year 2010, for which the effects were identified which produced unemployment in families where respondents stated that the phenomenon generates family instability, products of the low educational level and the shortage of jobs. Likewise made a diagnosis of the social economic policies of employment laid down by the present Government to reduce unemployment, where most indicated you are they are poor and they are not solving the problem. The study led to propose possible alternatives of solution to the problem of unemployment in the Quevedo canton, as the inhabitants surveyed consider lending to micro entrepreneurs and the creation of jobs to lessen the problem. The canton Quevedo, the 2010 census represents 21.5% of the total of the province of Los Ríos, which amounts to 173.575; the same one that has grown in recent years at a rate of 2.7 per cent annual average. 86.1% Of the population resides in urban Area. According to studies performed in several sources, such as newspapers, magazines and internet, believed that there is a sublime rate of unemployment, which is caused by various factors, which has influenced the social and economic development of the population. Most people do not know the reality of unemployment still found in the role of unemployed, do not know when you started, do not know what it really is the unemployment rate in Ecuador currently and is understood that this is a very important point that you need to know to be able to do something in this regard, because the number of unemployed is very large, but above all, most people do not know what are the main causes why there is unemployment in the present day, as it is the lack of academic preparation, in this case they should try to prepare more to overcome and so get a good job, another cause can be the own person lazy, people do not realize that the majority of the cases of unemployment are caused by themselves. The work is considered a necessary value that people have, but is currently only restricted to a part of the population. You have a decent job and keep it is the desire of those who are unemployed, outside the labor system and somewhat excluded from society, their status as unemployed. Unemployment can have profound effects, both on the individual and the society in which we live and which has a direct impact on the economy of the country and therefore of Quevedo. It imposes a cost in the economy to produce fewer goods and services, since the economic situation that currently exists does not generate sufficient sources of employment to recruit those who want and are willing to work, even if that service of unemployed labor is always lost. The field study found that the shortage of jobs generated unemployment and the policies implemented by the current Government of the Ec. Rafael Correa still not favored radically to the labor sector throughout the country.